KONSUMSI PAKAN AYAM RAS PETELUR FASE LAYER DI UPTD TAMAN TERNAK PASSO - Sarfan, Riri; Papilaya, Bercomien Juliet (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2023)
The success of raising poultry, especially laying hens, dipends on three pilars of animal husbandry, they are: seeds, feeds, and management. 60 – 70% of total production costs is feed. Therefore, the feed contant must meet a balanced portion of nutrients. Feed costs are determining factor for the success and failure of livestock raising businesses. The aim of community service activities is to provide skills and insight regarding feed management for laying hens in the layer phase in order to increase their productivity the stages of community service activities are: first, onservation second, implementation of activities for 1 month the benefite of community service activity is the breeders comprehend the correct use of feed for the fulfill meat of nutrients. In order to produce quality production. The result of community service is to determine the frequenly of feeding, 2 times a day with a amount of 120 grams per head per day in battery cages.